2015
DOI: 10.5194/acp-15-241-2015
|View full text |Cite
|
Sign up to set email alerts
|

Mapping CH<sub>4</sub> : CO<sub>2</sub> ratios in Los Angeles with CLARS-FTS from Mount Wilson, California

Abstract: Abstract. The Los Angeles megacity, which is home to more than 40 % of the population in California, is the second largest megacity in the United States and an intense source of anthropogenic greenhouse gases (GHGs). Quantifying GHG emissions from the megacity and monitoring their spatiotemporal trends are essential to be able to understand the effectiveness of emission control policies. Here we measure carbon dioxide (CO 2 ) and methane (CH 4 ) across the Los Angeles megacity using a novel approach -ground-ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
106
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 22 publications
(42 reference statements)
10
106
2
Order By: Relevance
“…If the emissions of CO 2 are known for a study location, the emissions of CO can be estimated by multiplying the correlation slopes and molecular mass mixing ratios (Wunch et al, 2009;Wong et al, 2015). Final emissions of CO will depend on choosing the values of the correlation slopes.…”
Section: Top-down Co Emissions From Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the emissions of CO 2 are known for a study location, the emissions of CO can be estimated by multiplying the correlation slopes and molecular mass mixing ratios (Wunch et al, 2009;Wong et al, 2015). Final emissions of CO will depend on choosing the values of the correlation slopes.…”
Section: Top-down Co Emissions From Observationsmentioning
confidence: 99%
“…The vehicular as well as industrial emissions contribute large fluxes of CO 2 and CO to the atmosphere in urban regions. Several simultaneous ground-based and aircraftbased studies of CO and CO 2 have been carried out in the past in different parts of the world (Turnbull et al, 2006;Wunch et al, 2009;Wang et al, 2010;Newman et al, 2013) but such a study has not been done in India except for recently reported results from weekly samples for three Indian sites by Lin et al (2015).…”
mentioning
confidence: 99%
“…As a proposed mission at this point in time, it is designed to measure high-resolution spectra of reflected sunlight in near-infrared bands and to deliver simultaneous retrievals of column-averaged dry air mole fractions of CO 2 , CH 4 , CO, and H 2 O (denoted XCO 2 , XCH 4 , XCO, and XH 2 O, respectively) at different times of day over North America. A prototype of the instrument on top of Mount Wilson, in the San Gabriel Mountains just north of Los Angeles, California, has been collecting high-quality data over that megacity since August 2011 (Key et al, 2012;Fu et al, 2014;Wong et al, 2015). The main scientific objectives of GeoFTS are the following:…”
Section: XI Et Al: Simulated Retrievals From Geostationary Orbitmentioning
confidence: 99%
“…7). For the first test, we filter out data where the observations differ from the Tracer-tracer relations were used for the TCCON (Wunch et al, 2009(Wunch et al, , 2016, CLARS (Wong et al, 2015, and in situ observations (Hsu et al, 2010;Wennberg et al, 2012). model above a threshold.…”
Section: Sensitivity Tests and Error Assessmentmentioning
confidence: 99%
“…CLARS has a viewing geometry that is more sensitive to the mixing layer than TCCON and nadir-viewing satellites, which leads to larger typical enhancements in CO 2 and CH 4 (Wong et al, 2015. For comparability we exclude enhancements from CLARS and in situ observations (e.g., in this section.…”
mentioning
confidence: 99%